2009
DOI: 10.1063/1.3104610
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence for the specific Na+ and K+ interactions with the hydrogen-bonded water molecules at the electrolyte aqueous solution surfaces

Abstract: Sum frequency generation vibrational spectra of the water molecules at the NaF and KF aqueous solution surfaces showed significantly different spectral features and different concentration dependence. This result is the first direct observation of the cation effects of the simple alkali cations, which have been believed to be depleted from the aqueous surface, on the hydrogen bonding structure of the water molecules at the electrolyte solution surfaces. These observations may provide important clue to understa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 59 publications
(123 reference statements)
4
30
0
Order By: Relevance
“…The decrease in the broad-band intensity of water SFG spectrum at low salt concentrations has also been reported by others. 25,26 Allen et al recorded the SFG spectra for 0.8 M NaF solution and 0.8 and 2 M solutions of NaCl, NaBr, and NaI. 19 Contrary to the other works, the SFG spectra did not vary much for 0.8 M solutions of NaF and NaCl.…”
Section: Introductionmentioning
confidence: 96%
“…The decrease in the broad-band intensity of water SFG spectrum at low salt concentrations has also been reported by others. 25,26 Allen et al recorded the SFG spectra for 0.8 M NaF solution and 0.8 and 2 M solutions of NaCl, NaBr, and NaI. 19 Contrary to the other works, the SFG spectra did not vary much for 0.8 M solutions of NaF and NaCl.…”
Section: Introductionmentioning
confidence: 96%
“…Aqueous interfaces play a fundamental role in many chemical, biological, and environmental processes including geo-mineralization/dissolution and atmospheric aerosol chemistry. , To advance our understanding of these processes, a molecular level picture of the aqueous interface itself is required. So far, water structure and ion distributions for mostly simple mono- and divalent salts at air/aqueous interfaces have been investigated by a variety of techniques including vibrational sum frequency generation (SFG) spectroscopy, second harmonic generation, photoelectron spectroscopy, X-ray reflectivity measurements, , as well as theoretical calculation and simulation. …”
Section: Introductionmentioning
confidence: 99%
“…Understanding the spatial extent to which the ionic effects are important is under debate. Recent studies demonstrate ion-induced long-range orientational order of bulk water molecules, and the long-range effects show specificity associated with the size and charge. , Smaller ions with larger charges tend to perturb water structures more effectively. While specific ionic effects have been observed at the air/aqueous interface, ,,,, those studies have focused mainly on alkali and alkaline earth metal ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In the 1990s Perera and Berkowitz found that heavy halide ions such as Br − and I − would accumulate at the air/water interface employing molecule dynamics (MD) simulations with a polarizable force field (FF). 10,11 Since then, the propensity of simple ions at the interface has been studied by a variety of surfacesensitive experimental [12][13][14][15] and theoretical approaches. [16][17][18][19][20][21] The specific effects that ions can play on protein stabilities 22 and chemical reactions at the interface 23 have also been realized.…”
Section: Introductionmentioning
confidence: 99%